EFEKTIVITAS PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Saryantono, Buang; Noviyana, Hesti (Epsilon: Jurnal Pendidikan Matematika, 2021)
Abstract: The ability to solve mathematical problems as one of the important skillsfor students who is also the goal of learning mathematics in the 2013 curriculum.The importance of problem solving skills is the basis for research objectives toanalyze the effectiveness of the Realistic Mathematics Education (RME) approachto the mathematical problem solving abilities of eighth grade students of SMPNegeri 23 Bandar Lampung, with research problems in the form of lowmathematical problem solving abilities of students. This study uses anexperimental method with a population of all eighth grade students of SMP Negeri23 Bandar Lampung which consists of 9 classes with a total of 287 students, whilethe sample is taken 2 classes, namely as an experimental class that applies theRME approach and as a control class that applies the conventional approach. Thesample was taken using the cluster random sampling technique. Measurement ofresearch variables using a test in the form of an essay as many as 5 questions thathave been tested for validity and reliability and declared as a good measuringtool. Hypothesis testing using parametric statistics in the form of t-test. The resultsof hypothesis testing show the value of t hit = 4.33 and at a significant level of 5%it is known that t daf = ????(1âˆ’????)= 1,67 means t hit > t daf so it can be concluded thatthe RME approach is effective in influencing students' mathematical problemsolving abilities class VIII SMP Negeri 23 Bandar Lampung. This situation is alsoseen from the average value of students' mathematical problem solving abilitieswhere the experimental class has a higher average value of 77 and the controlclass has an average value of 61.